COMORBID ANXIETY AS A DIFFERENTIAL TREATMENT PREDICTOR FOR TELEPHONE VERSUS FACE‐TO‐FACE ADMINISTERED COGNITIVE BEHAVIORAL THERAPY FOR DEPRESSION. Issue 11 (November 2014) - Stiles‐Shields, Colleen; Kwasny, Mary J.; Cai, Xuan; Mohr, David C.
<x xml:space="preserve">Abstract</x> Background The present study examines the role of comorbid anxiety on depression outcomes for those receiving cognitive behavioral therapy (CBT) for depression by telephone (T‐CBT) or face‐to‐face (FtF‐CBT). Methods Three hundred twenty‐five participants were randomized to T‐CBT or FtF‐CBT. Comorbid anxiety was measured using the Mini International Neuropsychiatric Interview and Generalized Anxiety Disorder 7. Depression was measured using the Hamilton Rating Scale for Depression and Patient Health Questionnaire 9. Results A hierarchical model including the two‐way interaction of treatment assignment and anxiety status indicated a significant effect for all outcome variables (Ps < .05). Post hoc t tests indicated T‐CBT participants with comorbid anxiety disorders had significantly higher symptom severity over time compared to their T‐CBT counterparts without anxiety (Ps < .001) and FtF‐CBT counterparts with comorbid anxiety (Ps < .003). There were no significant differences in outcomes between those with and without comorbid anxiety disorders receiving FtF‐CBT, or between T‐CBT and FtF‐CBT among those without comorbid anxiety disorders. Conclusions The findings indicate that the presence of baseline anxiety impacts the overall effect of T‐CBT for the treatment of depression.